2015
DOI: 10.1016/j.atherosclerosis.2015.10.011
|View full text |Cite
|
Sign up to set email alerts
|

The association of circulating 25-hydroxyvitamin D concentration with peripheral arterial disease: A meta-analysis of observational studies

Abstract: This meta-analysis suggests that low levels of circulating 25(OH)D are associated with PAD presence, particularly in patients presenting with CLI. These data suggest the possibility that vitamin D insufficiency may contribute to the development of more advanced PAD although this remains to be confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…The anti-inflammatory action of vitamin D was suggested to be mediated by an effect on calcineurin-mediated responses [116](Table 1). Further, a meta-analysis comprising six case-control studies assessing 6,418 patients with PAD suggests the association of low levels of circulating vitamin D with PAD and with chronic limb ischemia [17]. Li et al [18] and Oh et al [19] also reported similar association in their studies with 1,028 diabetic patients and 8,960 subjects, respectively.…”
Section: Vascular Diseasementioning
confidence: 89%
See 1 more Smart Citation
“…The anti-inflammatory action of vitamin D was suggested to be mediated by an effect on calcineurin-mediated responses [116](Table 1). Further, a meta-analysis comprising six case-control studies assessing 6,418 patients with PAD suggests the association of low levels of circulating vitamin D with PAD and with chronic limb ischemia [17]. Li et al [18] and Oh et al [19] also reported similar association in their studies with 1,028 diabetic patients and 8,960 subjects, respectively.…”
Section: Vascular Diseasementioning
confidence: 89%
“…Low levels of vitamin D have been associated with increased risk of CVD such as coronary artery disease (CAD) [5], myocardial infarction (MI) [67], hypertrophy [8], cardiomyopathy [9–10], fibrosis [1112], heart failure (HF) [1314]. In addition, deficiency of vitamin D has been found in arterial diseases, including aneurysm [1516], peripheral arterial disease (PAD) [1719], arterial calcification [20], hypertension (HTN) [2122] and atherosclerosis [23] (Figures 2 and 3). The low levels of vitamin D in these studies may be due to different confounding factors such as environment, age, sex, socioeconomic status, and nutritional status.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, many studies have reported an inverse association between serum 25(OH)D levels and cardiovascular risk. Low serum 25(OH)D concentrations (namely below 50 nmol/L) have been associated with increased risk of ischemic heart disease and myocardial infarction [5,6], heart failure [7][8][9], peripheral arterial disease [10], and cerebrovascular events [11,12]. However, the results of these studies may be limited by residual bias and reverse causality.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to cardiovascular disease, large epidemiological studies have routinely highlighted a link between vitamin D insufficiency or deficiency and increased risks of hypertension (Ke, Mason, Kariuki, Mpofu, & Brock, 2015), promotion of atherosclerosis (Kunadian, Ford, Bawamia, Qiu, & Manson, 2014; Nsengiyumva et al, 2015), chronic kidney disease (CKD) progression (Junarta, Jha, & Banerjee, 2019; Melamed et al, 2018), and cardiovascular mortality and morbidity (Wang, 2016; Wang et al, 2012). Vitamin D‐mediated suppression of the renin‐angiotensin‐aldosterone system (RAAS) appears to be the most likely mechanism through which vitamin D exerts its potential cardiovascular benefits.…”
Section: Introductionmentioning
confidence: 99%